1992
DOI: 10.1111/j.1439-0523.1992.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration from Callus Cultures of Allium trifoliatum subsp. hirsutum and Assessment of Genetic Stability by Isozyme Polymorphism

Abstract: Plant regeneration from callus cultures of Allium trifoliatum subsp. hirsutum fertile accession F-370, was studied as a means for clonal multiplication and germplasm storage of Allium spp. Callus was induced on in vitro-cultured basal leaf explants. Best proliferation was obtained on modified BDS medium supplemented with (mg/l): 0.75 picloram, 2.0 benzyl adenine, and 900 casein hydrolysate. Shoot and root organogenesis were obtained in 3 to 5 month old subcultured calli, on BDS or MS medium supplemented with (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Electrophoretic patterns of soluble leaf proteins were studied in extracts from field-grown plants and from regenerated plants produced in vitro, following explant cold-storage on several culture media . Isozyme analysis revealed identical banding pattern for all 13 proteins (Viterbo et al ., 1992) in all in vitro-produced plants . This is demonstrated here by the MDH profiles (Fig .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophoretic patterns of soluble leaf proteins were studied in extracts from field-grown plants and from regenerated plants produced in vitro, following explant cold-storage on several culture media . Isozyme analysis revealed identical banding pattern for all 13 proteins (Viterbo et al ., 1992) in all in vitro-produced plants . This is demonstrated here by the MDH profiles (Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Growth regulators were added at different concentrations, as detailed in the results . All cultures were kept in a growth room at 24 ± VC, and a 16 h photoperiod of cool-white fluorescent light (9 w/m 2 ) as described previously (Viterbo et al ., 1992) . For standard in vitro propagation, explants were subcultured in a fresh medium every 3 weeks .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations by van der Valk et al (1992) and Phillips & Hubstenberger (1987) demonstrated that A. fistulosum x A. cepa hybrids were particularly Table 1 Source Allium material and a list of the primary in vitro cultures produced since 1981. Refer to Novak et al (1986), Rabino witch & Brewster (1990), and Peffley (1992) Nair & Seo (1993), Peffley (1992), Pike & Yoo (1990), Rauber & Grunewaldt (1988), Havel & Novak (1988), Phillips & Hubstenberger (1987) Marani et al (1994, Nagakubo et al (1993), Havel & Novak (1988), Nagasawa & Finer (1988a), Ohkoshi et al (1987), Novak (1984), Maggioni & Marchesi (1984), Phillips & Luteyn(1983), Maksoud et al (1983) Buitveld et al (1993, Viterbo et al (1992), Rauber & Grunewaldt (1988), Nagasawa & Finer (1988b), Phillips & Hubstenberger (1987), Phillips & Luteyn (1983), Novak (1983), Oosawaetal. (1981) Seabrook (1994), Kahane et al (1992), Tashiro et al (1985), Phillips & Luteyn (1983) Rabinowitch & Brewster (1990, Havel & Novak (1988), Shahin & Kaneko (1986), Phillips & Luteyn (1983…”
Section: Genotype Effectsmentioning
confidence: 99%
“…The most efficient of the Novak et al (1986), Rabinowitch & Brewster (1990), and Peffley (1992 Keller (1990) Suh& Park (1984 callus systems are probably basal plate callus and embryo/seedling derived callus. Basal plate callus can regenerate de novo (Viterbo et al 1992) and should therefore contain a source of progenitor cells that should be both totipotent and competent to accept DNA. Field-grown onion bulbs are, however, very difficult to surface sterilise which restricts the amount of material readily available for transformation studies.…”
Section: Genotype Effectsmentioning
confidence: 99%